The importance of using Artificial Intelligence techniques in the fields of school learning and teaching - Karzoun, Noor Anees (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the importance of using artificial intelligence techniques in the fields of School learning and teaching. This study followed the descriptive qualitative approach, where an open-ended questionnaire was developed, and five female teachers who use techniques from different public schools affiliated with Ramallah and Al-Bireh Directorate participated in answering its questions. The results showed the importance of using AI techniques in school education in six areas: content presentation, teaching methods, Assessment, communication, teacher, and student. The results showed the importance of using AI techniques in the field of content; by adding excitement to the presentation, customizing and simplifying educational content. in the field of teaching methods; it contributes to creating an interactive environment, customized learning methods. In the field of Assessment; it contributes to saving time and effort, and achieving accuracy and objectivity. In the field of communication; it facilitates response, follow-up, and personal guidance. In the field of the teacher; it contributes to managing the teaching and learning process, providing sources and resources. In the field of the student; smart techniques contribute to meeting the individual needs of students and improving the learning process. Based on the findings, the researcher recommends launching the "Educational Creativity Using AI" award for the best procedural research or initiative that contributes to developing higher thinking skills among school students. and establishing a virtual training platform under the Palestinian Ministry of Education to provide programs and workshops on using AI techniques in education.
Keywords: Artificial Intelligence; School education; Importance of use; Techniques